The Effect of Sustainability Report Disclosure and Non-Performing Loans on Company Value Through Financial Performance at KBMI 3 and KBMI 4 Banks - Deriyansyah Deriyansyah; Indra Siswanti (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Fluctuations in the Price to Book Value (PBV) of KBMI 3 and KBMI 4 banks during 2021–2024 indicate that market valuation in the Indonesian banking sector remains sensitive to profitability and risk dynamics. While sustainability report disclosure and green finance have been increasingly promoted under the Sustainable Finance Roadmap, their direct contribution to firm value remains debatable. This study examines the effect of sustainability report disclosure, non-performing loans (NPL), and green finance on firm value, with financial performance as proxied by Return on Assets (ROA) as a mediating variable. Using panel data from 10 KBMI 3 and KBMI 4 banks listed on the Indonesia Stock Exchange over the 2021–2024 period, the analysis employs a Fixed Effects Model and mediation testing through path analysis. The results show that sustainability disclosure, NPL, and green finance do not directly influence firm value. However, ROA has a positive and significant effect on PBV. Sustainability reports and green finance significantly improve ROA, while NPL negatively affects it. Mediation testing confirms that financial performance bridges sustainability practices and credit risk management with firm value. This study demonstrates that sustainability initiatives contribute to firm value only when translated into measurable profitability, highlighting ROA as the critical transmission mechanism in Indonesian banking.